Pengembangan Alat Ukur Tes Fisik dan Keterampilan Cabang Olahraga Futsal berbasis Dekstop Program - Gumantan, Aditya; Mahfud, Imam; Yuliandra, Rizki (Journal of Sport Science and Education, 2021)
The objective of this research is new development in desktop-based program of futsal sport measurement test. The method used in this research is max method of qualitative, quantitative and development of brog and gral with ten stages. The results obtained in the large scale expert test material is a lecturer of sport measurement tests by 90%, media experts who are tested by computer experts by 87% and the test of Asian licensed trainer practitioners with 90% results. With results of more than 80% in the three initial test stages, small scale tests and up to large scale test stages, it can be concluded that research development is a new product in the futsal branch measurement sport test. Based on the result, it can be stated that this tool can be used effectively and efficiently.